The Development of Vulnerability Indicators for Homelessness: การพัฒนาตัวชี้วัดความเปราะบางในการเข้าสู่ภาวะไร้บ้าน - Tangtammaruk, Peera (Journal of Applied Economics and Management Strategy, 2022)
บทคัดย่อ งานวิจัยฉบับนี้มีวัตถุประสงค์เพื่อพัฒนาตัวชี้วัดความเปราะบางในการเข้าสู่ภาวะไร้บ้าน สำหรับกรณีของประเทศไทย โดยใช้การประมาณความเป็นไปได้สูงสุดจากแบบจำลองทางเศรษฐมิติ ทั้งนี้เนื่องจากในประเทศไทยยังไม่มีระบบการลงทะเบียนคนไร้บ้านจึงทำให้งานวิจัยฉบับนี้จึงต้องใช้แหล่งข้อมูลจากสองแหล่งที่แตกต่างกัน และผู้วิจัยได้ใช้แบบจำลองสองทางเลือกโดยใช้ข้อมูลจากลุ่มคนเปราะบางที่มีความเสี่ยงเป็นคนไร้บ้าน และ กลุ่มคนไร้บ้าน เพื่อหาความน่าจะเป็นและปัจจัยที่ส่งผลต่อภาวะไร้บ้านทั้งในระดับจุลภาคและระดับมหภาค ผลการศึกษา พบว่า รายได้ ความสัมพันธ์ในครอบครัว อายุ ทักษะในการสื่อสาร สถานะพิการ การดื่มแอลกอฮอล์ สิทธิในการเข้าถึงเบี้ยยังชีพผู้สูงอายุหรือคนพิการ และการได้รับเงินช่วยเหลือโควิด-19 เป็นปัจจัยที่มีนัยสำคัญสำคัญต่อความเปราะบางในการเข้าสู่ภาวะไร้บ้าน นอกจากนี้ผู้วิจัยได้นำค่าผลกระทบส่วนเพิ่มที่ประมาณได้จากแบบจำลองมาคาดการณ์จำนวนคนไร้บ้านภายใต้สถานการณ์จำลองที่แตกต่างกัน เพื่อให้เห็นถึงจำนวนและแนวโน้มของคนไร้บ้านในกรุงเทพมหานครและปริมณฑล สุดท้ายนี้แม้ว่าการประมาณการคนไร้บ้านจากแบบจำลองยังคงมีข้อจำกัด ผู้วิจัยหวังว่าผลการศึกษาจะสามารถนำไปพัฒนาต่อยอดเพื่อเป็นกลไกในการสร้างสัญญาณเตือนการเข้าสู่ภาวะไร้บ้าน ซึ่งเป็นหนึ่งในแนวทางการป้องกันปัญหาคนไร้บ้านในประเทศไทยได้ต่อไป ABSTRACT This paper attempts to develop the homeless early warning indicators for the case of Thailand using maximum likelihood estimation. Since there is no homeless registration system in Thailand, this paper has to use two different sources of data in order to estimate homelessness probability. We designed an econometric binary choices model in which one group is a group of vulnerable non-homeless people, while another is a group of homeless people. The objectives of our model are to find the homeless probabilities of all possible related factors, and to estimate homeless probabilities in both micro and macro level. This paper finds that income, family relationship, age, communication skill, handicapped status, alcohol consumption, right to elderly or handicapped allowance, and receiving covid-19financial support were significant factors affecting individual probability to be homeless. In addition, the marginal effects estimated from the model enables us to interpret as the homeless early warning indicator, predict individual probability to be homeless, as well as forecast number of homeless people in Bangkok Metropolitan Region under different simulated circumstances. Finally, besides the estimation limitation, we still hope that these early warning indicators could be further developed to support homeless prevention policy in Thailand.